The Absence of Presence and the Presence of Absence: Social Distancing, Sacraments, and the Virtual Religious Community during the COVID-19 Pandemic - Parish, Helen (Religions (Basel, Switzerland ), 2020)
The response of churches to the challenges presented by the global COVID-19 pandemic invites a closer examination of the relationships between virtual and embodied religious communities during a time of social distancing. The speed and the scale of the closure of church buildings during Easter 2020 sheds light upon the multiplicity of practical, emotional, and spiritual responses to a relationship between church and people that is increasingly dominated by online interactions. Such a seismic shift in social culture opens up the possibility and challenges of a new understanding of belonging and participation in a religious community. Given its liturgical, pastoral, and sacramental significance, Easter 2020 was a highly charged moment for the relationship between the Christian churches and the faithful, and between religious worship and social media. In the shift from embodied community to virtual congregation that followed, the material absence of physical presence in collective worship was striking, as was the psychological presence of that absence. This paper analyses different understandings of religion, church, and community in the period of a pandemic, and argues for the value of an approach that situates the debates spawned in the context of historical precedent, personal experience, and theoretical approaches to networks, communities, religion, and social media.